Effect of fentanyl nasal packing treatment on patients with acute postoperative pain after closed reduction of nasal bone fracture: a randomized double-blind controlled trial. Issue 3 (4th May 2019) - Kim, Kwan-Sub; Yu, Sung Chul; Han, Jung-Woo; Shim, Sung-Min; Kwak, Soohyun; Kim, Yong-Min; Kim, Seong-Su
Abstract: Purpose: Nasal bone fracture reduction surgery is normally followed by nasal packing to control bleeding. Yet, patients suffer from pain and require further analgesic treatments following nasal packing and removal. This study aimed to evaluate the effect of fentanyl-soaked packing as a method of controlling pain after nasal surgeries in a prospective, randomized, double-blind controlled trial. Methods: Sixty-five patients that have undergone closed nasal bone fracture reduction surgery were included in this study. Thirty-two patients were treated postoperatively with 50 mcg fentanyl-soaked Merocel ®, a biodegradable synthetic polyurethane foams packing, and the other 33 patients were treated with saline-soaked packings. To analyze the relative nasal pain control effect of fentanyl, Numeric Rating Scale, patient satisfaction and Ramsay Sedation Scale were used. Patients were closely monitored to record relevant cardiopulmonary indicators and degree of adverse symptoms such as headache or sore throat. Results: Fentanyl group had a significantly lower Numeric Rating Scale and higher patient satisfaction for most of the time periods after operation ( p  < .05). Symptoms of headache and sore throat were also significantly reduced. Ramsay Sedation Scale scores improved compared to the control group ( p  < .05). No significant differences in cardiopulmonary relevant indicators between the two experimental groups were observed ( p  > .05). Conclusion: Fentanyl-soaked packing significantly decreased postoperative pain with no observable adverse effects. Our results demonstrate that topical fentanyl application to nasal packing is an effective method of postoperative pain control after closed nasal bone fracture reduction surgery.